Endoscopic resection in the duodenum: current limitations and future directions - Bourke, M. J. (Endoscopy, 2013)
Duodenal lesions that should be considered for endoscopic resection comprise a heterogeneous group of disorders. Most are adenomas, primarily located in the descending duodenum. In comparison to lesions of a similar size elsewhere in the gastrointestinal tract, the risk of major complications from endoscopic resection of duodenal lesions is magnified. The unique anatomical features of the duodenum are largely responsible for this, but despite this we continue to apply conventional endoscopic therapies when a more sophisticated approach is required. Many other important clinical questions in relation to duodenal adenomas remain unanswered. This review aims to identify the gaps in the knowledge base and therapeutic approach and propose some solutions and directions for future research.